Analisis Berita Pencalonan Gubernur Dan Wakil Gubernur NTT Tahun 2018 Pada Surat Kabar Victory News: Sebuah Kajian Wacana Kritis - Fransiskus Rolantus Lagut; Feliks Tans; Marselus Robot (SASDAYA: Gadjah Mada Journal of Humanities, 2021)
This study aims to analyze the text, the practice of citizenship and the socio-cultural context in the news text of the election of the governor and vice governor of East Nusa Tenggara in 2018 in the Victory News newspaper. The theory used in this study is Norman Fairclough's critical discourse analysis to analyze texts, the practice of producing and consuming texts, and socio-cultural practices on texts. The method used is descriptive qualitative method. From the data analysis, conclusions can be drawn. First, the VN news text features the 'promise' vocabulary which tends to be used to weaken the pair of candidates for governor-vice-governor besides Viktory-Joss. Transitive sentences tend to be used in the headline of VJ packages while other packages tend to be intransitive sentences. The use of negative sentences and metaphors tends to be used to benefit VJ packages. The news texts used by Victory News tend to be descriptive and argumentative in nature, characterized by the use of meaningful causal conjunctions. Second, Victory News discourse tends to raise news about the campaign, vision and mission, the strength of character and background that supports the Viktory-Joss package. Victory News tends to be political, which means that the interests of the owners of these newspapers are more dominant than balanced reporting. Third, Victory News ideology is positive imaging by highlighting the VJ package so that the public positively evaluates the vision, missions, and actions taken by the package